ANALYZING LAND SUITABILITY FOR INDUSTRIAL AREAS IN PEKANBARU CITY USING THE SMCE METHOD AND GEOGRAPHICAL INFORMATION SYSTEMS - Aisyah, Siti; Dimyati, Muhammad (UI Scholars Hub, 2024)
Domestic industrial growth continues to increase in line with population growth and the development of new areas, both in the city center and on the outskirts of the city. The location of Riau Province, which is close to Malaysia and Singapore, makes it an attractive investment destination, supported by Riau's abundant natural resources. Pekanbaru City, as the capital of Riau Province, consisting of 12 regencies/cities, serves as the center of government and economy. Among the 27 integrated industrial estates, there are two locations in Riau Province determined by the central government in the 2020-2024 RPJMN, namely Tanjung Buton in Siak Regency and Tenayan Raya in Pekanbaru City. Therefore, it is necessary to analyze the suitability of the land for industrial areas in Pekanbaru City, ensuring compliance with the Pekanbaru City Spatial Plan, as well as provincial and national spatial plans. The method used is SMCE (Spatial Multi-Criteria Evaluation) and Geographic Information System, taking into account physical variables such as distance from roads, rivers, settlements, and slopes. The results of spatial data processing will be overlaid with the map of the Tenayan Industrial Area in the Pekanbaru City Spatial Planning.